Synthesis and Application of Bisazo Acid Dyes for Water Repellent Polyamides - TELI, M.D.; SEKAR, N.; PRABHU, K.H. (Asian Journal of Chemistry, 2010)
Simultaneous dyeing and finishing of textiles is known for its potential to reduce the cost, increase production and drastically reduce the effluent load. However, some of the finishes applied during dyeing or post dyeing operation are found to show lowering in performance properties due to their poor durability to washing. The present paper reports the results of the synthesis and application of bisazo acid dyes containing m-trifluoromethyl aniline and m-toluidine/p-nitro aniline reacted with the coupler H-acid, on the polyamide fabrics mainly silk, wool and nylon interms of wettability, water repellency, colour depth and fastness. The improved and durable water repellency with good performance properties was obtained in case of dyes containing trifluoromethyl group and p-nitro aniline.